2011
DOI: 10.1007/s11670-011-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Shu-Gan-Liang-Xue decoction simultaneously down-regulates expressions of aromatase and steroid sulfatase in estrogen receptor positive breast cancer cells

Abstract: The results suggest that SGLXD is a potential dual aromatase-sulfatase inhibitor by simultaneously down-regulating the expressions of CYP19 and STS in MCF-7 and T47D cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Aromatase is also the target of AIs, which are widely used in breast cancer endocrine therapy at present. Previous research by our group indicated that SGLXD, the original form of mSGLXD, simultaneously downregulated aromatase and steroid sulfatase at transcription and protein levels in ER-positive breast cancer cell lines MCF-7 and T47D ( 44 ), which may underlie the anti-tumor mechanism of SGLXD. Therefore, SGLXD may have synergistic inhibitory effects on aromatase with AIs to a certain extent.…”
Section: Discussionmentioning
confidence: 90%
“…Aromatase is also the target of AIs, which are widely used in breast cancer endocrine therapy at present. Previous research by our group indicated that SGLXD, the original form of mSGLXD, simultaneously downregulated aromatase and steroid sulfatase at transcription and protein levels in ER-positive breast cancer cell lines MCF-7 and T47D ( 44 ), which may underlie the anti-tumor mechanism of SGLXD. Therefore, SGLXD may have synergistic inhibitory effects on aromatase with AIs to a certain extent.…”
Section: Discussionmentioning
confidence: 90%
“…Sarcococca saligna, the sweet box or Christmas box, native from Northern Pakistan, contains phytochemical constituents such as alkaloid-C, dictyophlebine, sarcovagine-D and saracodine, which inhibit aromatase [86]. Shu-Gan-Liang-Xue decoction (SGLXD) is a traditional Chinese herbal formula with a potential dual aromatase-sulfatase inhibitor by simultaneously down-regulating the expressions of aromatase and sulfatase in BCa cell cultures [87]. SGLXD also has anti-tumor effects on the BCa cells ZR-75-1 by inhibiting aromatase and steroid sulfatase [88].…”
Section: Natural Compounds Inhibiting the Steroid Synthesismentioning
confidence: 99%
“…Melatonin [44] Naringin, apigenin, berberine, palmatine, bavachin, jatrorrhizine, bavachinin [80] Alangenes [82] Extracts of Brassaiopsis glomerulata [84] Bakuchiol [85] Extracts of Sarcococca saligna [86] Shu-Gan-Liang-Xue decoction [87,88] Aqueous extracts of white button mushrooms [90] Butein [89] Obacunone [91] 5α-reductase Finasteride [53] Dutasteride [54] Serenoa repens extracts [92] Ethanolic extracts of Epilobium angustifolium [93] (−)-epigallocatechin gallate, biochanin A, daidzein, genistein, kaempferol [94] caffeic acid, grandifloroside [95] polyphenols from Cynomorium songaricum [96] Androgen receptor (SARM) Bicalutamide [65] Enzalutamide [69] Darolutamide [71] Methanolic extract of Brosimum rubescens bark [98] 3,3 -diindolylmethane [99] Androgen receptor (SARD) Darolutamide derivatives [79] Tanshinone IIA [100] Ethanolic extracts from propolis [101] Estrogen receptor (SERM)…”
Section: Pharmacological Targets Synthetic Compounds Natural Compoundsmentioning
confidence: 99%
“…Appropriate safety of SGLXD has been shown in herb-drug safety/interaction studies [39,59,73,[76][77][78][79][80][81][82][83][84][85][86][87][88][89]. This preliminary research has been limited to China, with Chinese breast cancer survivors and in a Chinese hospital setting.…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%